1998
DOI: 10.1038/bjc.1998.609
|View full text |Cite
|
Sign up to set email alerts
|

Seventeen-year evaluation of breast cancer screening: the DOM project, The Netherlands

Abstract: Summary The DOM project is a non-randomized population-based breast cancer screening programme in Utrecht which started in 1974-75.The 17-year effect has been evaluated by a case-control study of breast cancer deaths dunng the period (Weiss and Lazovich. 1996). was ealuated by excluding breast cancer deaths wvith a short follovi-up period after diacnosis (i.e. deaths of patients wvho viere less likely to hax-e been screened). because their inclusion wiould gixe the impression of a disproportionately large n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 12 publications
3
19
0
Order By: Relevance
“…From other case -control screening studies, there is a range of results from a very small benefit to large reductions in mortality as observed in this study (Palli et al, 1989;Mittenburg et al, 1998;Fielder et al, 2004;Elmore et al, 2005;Gabe et al, 2007). Our estimated benefit may be slightly biased in favour of screening by the selection of recently diagnosed cases (1995 -2004), which will of necessity be relatively rapidly fatal and therefore may underrepresent screening-exposed fatal cancers.…”
Section: Discussionmentioning
confidence: 54%
“…From other case -control screening studies, there is a range of results from a very small benefit to large reductions in mortality as observed in this study (Palli et al, 1989;Mittenburg et al, 1998;Fielder et al, 2004;Elmore et al, 2005;Gabe et al, 2007). Our estimated benefit may be slightly biased in favour of screening by the selection of recently diagnosed cases (1995 -2004), which will of necessity be relatively rapidly fatal and therefore may underrepresent screening-exposed fatal cancers.…”
Section: Discussionmentioning
confidence: 54%
“…The optimal screening interval has been investigated and a study by White et al [18] found no evidence that American female patients aged $50 years who undergo biennial mammography screening have an increased risk of late-stage breast cancer compared with patients who undergo annual screening. However, results from other studies are inconsistent regarding the relative advantages of 1-year vs 2-year screening intervals [19,20], and a study from Finland estimated the effectiveness of intensive screening with poor attendance to be the same as that of infrequent screening with a high attendance rate [21]. It is obvious that finding an optimal screening interval in an organised screening setting is a complex issue, owing to individual characteristics and social conditions.…”
Section: Discussionmentioning
confidence: 92%
“…About 45% of the controls were screened more than once in the index period (18% of the cases). Several other case-control studies found that the effect of screening on the risk of breast cancer mortality increases with the number of screens (4,28,29). Further analysis showed that the majority of the reduction observed is particularly due to nonattendance of screening examination among those who received their first invitation between age 70 and 75 years: 19% (27 of 141) of the controls never attended screening compared with 82% of the cases (23 of 28).…”
Section: Discussionmentioning
confidence: 98%